Agrochemical characterization of vermicomposts produced from residues of Palo Santo (Bursera graveolens) essential oil extraction - Carrion Paladines, H. (2016)
Fruits of Palo Santo (Bursera graveolens) are used for essential oil extraction. The extraction process is very efficient, because up to 3% of the fresh fruits can be transformed into essential oil; however, a considerable amount of waste is concurrently produced (>97% of the fresh biomass). Recent developments in Ecuadorian policies to foster environmentally friendly agroforestry and industrial practices have led to widespread interest in reusing the waste. This study evaluated the application of four vermicomposts (VMs), which are produced from the waste of the Palo Santo fruit distillation in combination with other raw materials (kitchen leftovers, pig manure, goat manure, and King Grass), for agrochemical use and for carbon (C) and nitrogen (N) decomposition in two soils with different textures. The results showed that the vermicompost mixtures (VMM) were valuable for agricultural utilisation, because total N (min. 2.63%) was relatively high and the C/N ratio (max. 13.3), as well as the lignin (max. 3.8%) and polyphenol (max. 1.6%) contents were low. In addition, N availability increased for both soil types after the application of the VMM. In contrast, N became immobile during decomposition if the VM of the pure waste was added. This likely occurred because of the relatively low total N (1.16%) content and high C/N ratio (35.0). However, the comparatively low C decomposition of this VM type makes its application highly recommendable as a strategy to increase the levels of organic matter and C, as well as for soil reclamation. Overall, these results suggest that the residues of the Palo Santo essential oil extraction are a potential source for vermicompost production and sustainable agriculture.